Recent Progress in Macromolecular Design and Synthesis of Bile Acid‐Based Polymeric Architectures. Issue 3 (21st December 2021) - Sahoo, Subhasish; Ghosh, Pooja; Khan, Md Ezaz Hasan; De, Priyadarsi
Abstract: Macromolecular engineering presents a pleasant tactic for planning the construction of desired molecular architectures from nano to macro configurations. The mechanistic pathways and synthetic features of macromolecular designs mostly rely on the precursor composition, topology, functionality, and complexity in architectures. Specifically, macromolecular design with biomolecular conjugation has attracted remarkable attention due to its typical biochemical and physiological affirmative traits. In this review article, it is intended to highlight the major progress on the macromolecular designs and synthesis of polymers comprising bile acid (BA) as the biomolecular colleague. BAs are steroidal biocomposites, produced through cholesterol metabolism in the bile of mammals and vertebrates. They are low priced, biocompatible, abundant, trivially toxic, and structurally unique for facewise amphiphilicity, which make them suitable for designing BA‐based polymers (BAPs) to be utilized in biomedical fields. The major aim of this review article is to summarize the recent progress (2015–present) on the requisite necessity of BA in BAPs toward design and synthetic avenues. In particular, the design of various polymers with primary and secondary BAs at side chain, main chain, chain end, crosslinking zone, and core confined area are illustrated in this review article via numerous reported methods. Abstract : In this review article, the design and synthetic strategies of various polymers with primary and secondary bile acids (BAs) at side chain, main chain, chain end, crosslinking zone, and core confined area are highlighted via numerous reported literatures. The fascinating outcomes from various literature reports have led to bile acid‐based polymeric materials being utilized in various biomedical applications.